The Relationship between Tourist Satisfaction on Marketing SIM, Information Quality and Service Quality on Tourist Loyalty in The Colorful Village of Malang City - Crames, Anibal Mario Joao Indami; Pratama, Bestio Putra; Ladystia, Arini (Jurnal Pariwisata Tourista, 2023)
Malang City Tourism has become one of the tourist destinations favored by visitors, with a good Marketing SIM from tourist destinations, the quality of information provided by these tourist destinations, and the quality of service when tourists visit these tourist destinations. The purpose of this study was to analyze the impact of the existence of a marketing sim, information quality, and service quality on tourist loyalty in the Colorful Village of Malang City through tourist satisfaction. The population in this study were all people who had visited Kampung Warna Warni Malang City, with a total sample of 105 respondents and in this study the data analysis technique used was path analysis. The results of this study found that marketing SIM and service quality had a direct effect on tourist loyalty, while information quality did not have a direct effect on tourist loyalty. The results of this study also showed that marketing SIM, information quality and service quality had an effect on tourist loyalty through tourist satisfaction which can be interpreted that tourist satisfaction really mediates in this study. The conclusion that can be drawn is that tourists who are loyal to the tourist destination of the Colorful Village of Malang City are tourists who are satisfied with the marketing SIM, quality of information, and quality of service in the Colorful Village of Malang City.